PENGARUH HUBUNGAN KERJA, PENGALAMAN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN BANK CENTRAL ASIA (BCA) CABANG BOROBUDUR, MALANG - Laniwidyanti - -; Noermijati - -; Armanu - Thoyib (Sekolah Pascasarjana Universitas Brawijaya, 2010)
ABSTRACT This study analyzed effects of working relationship, working experience and working motivation toward the employees’ performance in Bank Central Asia (BCA) Branch of Borobudur Malang, either simultaneously or partially, as well as the dominant effect toward performance of the employees. This study was conducted in Bank Central Asia (BCA) Branch of Borobudur Malang, including : KCP Lawang, KCP Singosari, KCP Blimbing, KCP Tumpang, with the number of sample 109 persons comprising of 17 managers and 92 employees to identify the effect of working relationship, working experience and working motivation toward the employees’ performance, therefore multiple regression analysis was applied. Results of the study concluded that : (1) The result of the study simultaneously indicated that the variables of the study, working relationship, working experience, and working motivation have significant effect toward the employees’ performance in Bank Central Asia (BCA) Branch of Borobudur Malang, (2) The result of the study partially indicated that the respective variables including working relationship, working experience, and working motivation has significant effect toward the employees’ performance in Bank Central Asia (BCA) Branch of Borobudur Malang. Among the variables, the dominant one is the variable of working motivation. Keywords: working relationship, working experience, motivation